Case report: Mixed infection of bovine papillomaviruses associated with squamous papilloma of the upper alimentary tract in a dairy cow - Fernandes, Kamila Peruchi; Alfieri, Amauri Alcindo; Darold, Gabriela Molinari; Boabaid, Fabiana Marques; Dall Agnol, Alais Maria; Lunardi, Michele (Frontiers in Veterinary Science, 2022)
Bovine papillomavirus (BPV) infection can induce neoplastic lesions in both cutaneous and mucosal epithelia in cattle. This study describes the BPV types associated with proliferative lesions with diverse histopathological features present in the upper alimentary tract of a dairy cow suffering from chronic diarrhea from Midwestern Brazil. At autopsy, warts and plaques composed of multiple spherical nodules were observed in the esophageal mucosa, the areas surrounding and constricting the opening of the cardia, and the rumen pillars. One esophageal papillomatous proliferative lesion and a smooth-surfaced proliferative lesion located at the rumen entrance were evaluated by histopathological and molecular analyses. PCR amplification of partial fragments of the BPV L1 and E1 genes was performed followed by sequencing of the obtained amplicons. Upon histopathological evaluation, the esophageal lesion was classified as a squamous papilloma, whereas the other ruminal proliferative lesion consisted of a fibropapilloma. Direct sequencing of PCR products obtained from ruminal fibropapilloma DNA revealed the presence of BPV2. Sequencing of inserts from selected clones containing partial fragments of the BPV L1 and E1 genes revealed a mixed infection of BPV types 2 and 4 in the esophageal squamous papilloma. The findings reported in our investigation reinforce the association of BPV with benign lesions of the bovine alimentary tract in both single and mixed infections, as previously demonstrated to occur in a buffalo. In addition, this report represents the documentation of the occurrence of massive alimentary papillomatosis associated with BPV types 2 and 4 in cattle raised on lands without infestation by bracken fern in Midwestern Brazil.